2023
DOI: 10.1055/a-2038-0476
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dietary Niacin Intake with Diabetes in Adults in the United States

Abstract: Objective: Previous studies have shown inconsistent associations between niacin supplementation and diabetes, and little is known about the relationship between dietary niacin intake and risk of diabetes in the general population. Our study aimed to explore the association between dietary niacin intake and risk of diabetes in the adult population in the United States. Methods: Data from the 2005–2016 National Health and Nutrition Examination Surveys were analyzed. Diabetes was diagnosed according to the Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Niacin might influence DNA repair, genomic stability, and the immune system, eventually impacting cancer risk, but its metabolism requires complex interactions [ 52 ]. Moreover, it can be influenced by numerous factors such as income, education level, race, and comorbidity [ 66 ]. To date, identifying the correct dose for cancer prevention is challenging since niacin intake is highly variable across the population, exceeding the tolerable upper intake level [ 66 ], and some uncertainty exists about the potential benefit, even in other conditions (diabetes, cardiovascular disease, and neurological disorders) [ 52 , 66 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Niacin might influence DNA repair, genomic stability, and the immune system, eventually impacting cancer risk, but its metabolism requires complex interactions [ 52 ]. Moreover, it can be influenced by numerous factors such as income, education level, race, and comorbidity [ 66 ]. To date, identifying the correct dose for cancer prevention is challenging since niacin intake is highly variable across the population, exceeding the tolerable upper intake level [ 66 ], and some uncertainty exists about the potential benefit, even in other conditions (diabetes, cardiovascular disease, and neurological disorders) [ 52 , 66 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the studies regarding vitamin B3 demonstrate a more contradictory picture. While cross-sectional studies have indicated an inverse correlation [ 20 , 21 , 22 ], Pan et al have reported a positive correlation, underscoring the complexity of this relationship [ 23 ]. Folic acid (vitamin B9) presents another intriguing case.…”
Section: Introductionmentioning
confidence: 99%